Search for Barents: Evaluation of Possible Burial Sites on North Novaya Zemlya, Russia - Zeeberg, Jaapjan J.; Floore, Pieter M.; Maat, George J.R.; Gawronskli, Jerzy H. (ARCTIC, 2002)
Three cairns on northernmost Novaya Zemlya identified as possible rock-pile graves by Russian investigators in 1977 and 1988 were located and inspected for human remains. These cairns are in the area visited by Dutch seafarers between 17 and 22 June 1597, after their wintering on Novaya Zemlya, and may contain the body of Willem Barents. Barents and one of his crewmen died on 20 June 1597 while the winterers were on landfast ice close to shore. Previous research on Spitsbergen and contemporary reports on the efforts of 16th and 17th century Dutch seafarers to prepare a Christian grave led us to conclude that the deceased probably were buried on the beach, possibly in a shallow grave or a snowbank. Inspection of the area indicates that this grave probably was destroyed by high (5+ m asl) wave run-up during storms, cryogenic erosion, and animals (polar bear, fox). None of the cairns, or any of several other prominent rock piles in the ~180 km long search area, contained human remains or had lichen growths that would indicate construction ~400 years ago (>2 cm, Rhizocarpon sp.). Cairns were not reported by the Dutch in 1594-98, and most of those encountered on northern Novaya Zemlya probably date from exploration after ca. 1860, when the region north of ~76°N became accessible in a warming, post-Little Ice Age climate. Trois cairns situés aux confins septentrionaux de la Nouvelle-Zemble et identifiés en 1977 et 1988 par des chercheurs russes comme pouvant signaler des amas de pierres funéraires ont été localisés et ont fait l'objet d'une inspection en vue de déterminer s'ils renfermaient des restes humains. Ces cairns se trouvent dans la région visitée par des navigateurs néerlandais entre le 17 et le 22 juin 1597, après leur hivernage en Nouvelle-Zemble, et ils auraient pu contenir le corps de Willem Barents. Ce dernier et un membre de son équipage périrent le 20 juin 1597, alors que les hivernants se trouvaient sur la glace près du rivage. Des recherches antérieures sur le Spitzberg et des rapports ...